Let farmers judge :a joint World Bank-African Development Bank evaluation / (Acc: 1097) a joint World Bank-African Development Bank evaluation - Hiemstra, Wim.; Reijntjes, Coen.; Werf, E. J. van der. (London, U.K. : Intermediate Technology Publications, 1992)
Contributed articles.
Keywords: Sustainable agriculture; Sustainable agriculture; Agriculture